Քրիստոնեության մուտքն Աղվանք եւ հարակից երկրներ - Հենրիկ Սվազյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Согласно одного из церковных преданий, христианство в северо-восточные края Великой Армении и в страны Чор и Алуанк (Кавказскую Албанию) проникло в первой половине II века благодаря проповеднической деятельности св. Егише — ученика апостола Фаддея. Усилиями его были основаны христианские общины, в Гисе была построена церковь — первая в северо-восточных краях Армении, и была создана прочная основа для распространения христианства. According to one of the church-traditions, Christianity was introduced in North-Eastern regions of Magna Armenia and in the countries Chor and Albania in the first half of 2nd century, thanks to the missionary efforts of St. Eghisha, disciple of the apostle Thaddeus. Thanks to his endless efforts Christianity was solidly ancred in these districts; in Gis, one of the newly erected cathedrals became the important center for the evangelization of the Caucasian Albania.
Keywords: History; Auxiliary Sciences of History; Ancient History; Christianity; Archaeology